Influence of Mass Media on Academic Performance of Secondary School Students in Nigeria and Strategies for Improvement - Ukpabi, I. D.; Muibi, T. G.; Ojedeji, S. O. (Journal of Research in Adult and Continuing Education, 2025)
This paper discussed the influence of mass media on academic performance of secondary school students in Nigeria and strategies for improvement. Mass media are various channels or tools used to communicate information, news, and entertainment to a large audience. These channels or tools can be traditional or modern, and they play a crucial role in shaping public opinion, influencing culture and providing information to the masses. The paper explored the various forms of mass media accessible to secondary school students in Nigeria, the patterns and frequency of media consumption among students, the perceived positive and negative influences of mass media on students’ academic performance, and the sociocultural factors that shape students’ media habits. The study recommended that students should have limited access to mass media. Parents and teachers should be their controllers and encourage them to watch and listen to programmes that are educative. Parents should be aware of the positive and negative impact of access to mass media on their children. Parents, teachers and guardians should ensure that children spend most of their time reading, playing with others and doing their homework in order to ensure high performances. Keywords: Addiction, Academic Performance, Students, Mass media.